Simulation of Single Cylinder Engine Fuel with Alternative Fuel by Using Available Software - Muhammad Syahir, Ali; M. T., Musthafah; A. M., Mohd Shafie; R. A., Bakar (Praise Worthy Prize, 2014)
Simulation study, which is one –dimensional by using available software (GT-Power) was used to study the performance of the single cylinder engine with different types of fuel source. In this study, two different types of fuel were used which are gasoline and natural gas. The simulation was run based on models built in Gt-power and the model were validated by measurement from the real engine.